العمل من أهم عوامل الإنتاج من المنظور إسلامي دراسة تطبيقية ولاية النيل الأبيض للفترة من 2008م - 2014م - د. صلاح محمد ابراهيم أحمد, (White Nile Journal for Studies and Research, 2026)
The study concluded that Islam urges work and ordered everyone is able to work and rejects unemployment and poverty Kmadaah of poverty and destitution and disrupt production. The work and eaming project and the pursuit of livelihood arab honor of man and pleasing to the Lord and for the benefit of the community and to satisfy the needs of undisciplined verdicts and Islamic preference productive spending on consumer spending and then give Isiam a preference for project work to worship as that islam is a religion of work and treatment, production and reconstruction of the land and repairing the economic conditions of communities and ensure the rights and dulles and the distribution of wealth for individuals fairly. The study also found that the most important results the following proportion of the labor rates mandate amounted to 36% of the total population of the state of male and female types, where the proportion of the work amounted to 20% in males and females at 10%. As unemployment reached 48% in females and the percentage of poverty rates of 55% to the mandate of the Write Nie, compared with rates of poverty in Sudan, which amounted to 46% And also exited the study recommendations following: should the state sock government for the establishment of projects to ensure that the work and provide wide opportunities to work as a graduate product and microfinance for families producing and creating enough jobs to absorti as much of the labor for the elimination of unemployment, poverty and destitution urged everyone jurisdiction over labor. religious and social value,